Extracellular Vesicles and DAMPs in Cancer: A Mini-Review - Abu, Nadiah; Rus Bakarurraini, Nurul Ainaa Adilah; Nasir, Siti Nurmi (Frontiers in Immunology, 2021)
Certain cancer therapy has been shown to induce immunogenic cell death in cancer cells and may promote tumor progression instead. The external stress or stimuli may induce cell death and contribute toward the secretion of pro-inflammatory molecules. The release of damage-associated molecular patterns (DAMPs) upon induction of therapy or cell death has been shown to induce an inflammatory response. Nevertheless, the mechanism as to how the DAMPs are released and engage in such activity needs further in-depth investigation. Interestingly, some studies have shown that DAMPs can be released through extracellular vesicles (EVs) and can bind to receptors such as toll-like receptors. Ample pre-clinical studies have shown that cancer-derived EVs are able to modulate immune responses within the tumor microenvironment. However, the information on the presence of such DAMPs within EVs is still elusive. Therefore, this mini-review attempts to summarize and appraise studies that have shown the presence of DAMPs within cancer-EVs and how it affects the downstream cellular process.